THE EFFECT OF VOCABULARY MASTERY TOWARD THE READING COMPREHENSION SKILL FOR THE STUDENTS GRADE VIII IN THE STATE OF JUNIOR HIGH SCHOOL IN BEKASI DISTRICT - Mukhlasul Fasikh (STIBA IEC JAKARTA, 2018)
This study aims to check out the effect of vocabulary mastery toward the reading comprehension skill in the State of Junior High School in Bekasi District. The method used in this research is expose facto with the correlation and regression analysis that is connecting between data showing the level vocabulary mastery toward the reading comprehension skill of students in the State of Junior High School in Bekasi District. Sampling was done by random sampling technique. The respondents are 80 students in this research. The research instruments were the test questions with multiple choice forms. The result showed that there is a significant influence of vocabulary mastery toward the reading comprehension skill of English Language on students Grade VIII in the State of Junior High School in Bekasi District. This is evidenced by the acquisition of Sig value. 0.003 <0.05 and th = 3.019. Variable vocabulary mastery contributed 13.86% in improving the reading comprehension skill